2004
DOI: 10.1126/science.1102612
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of Cardiac Defects in Id Knockout Embryos by Injection of Embryonic Stem Cells

Abstract: We report that Id knockout mouse embryos display multiple cardiac defects but mid-gestation lethality is rescued by injection of 15 wild type ES cells into mutant blastocysts. Myocardial markers altered in Id mutant cells are restored to normal throughout the chimeric myocardium. Intraperitoneal injection of ES cells into female mice prior to conception also partially rescues the cardiac phenotype with no incorporation of ES cells. IGF1, a long-range secreted factor, in combination with WNT5a, a locally secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
184
1
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(188 citation statements)
references
References 22 publications
2
184
1
1
Order By: Relevance
“…ID proteins form DNA-binding incompetent heterodimers with bHLH transcription factors thereby inhibiting their transcriptional activities (Benezra et al, 1990). Individual ID-proteins have been linked to inhibiting cellular differentiation, inhibition of bHLHand other transcription factors (Benezra et al, 1990;Jen et al, 1992;Kreider et al, 1992;Ohtani et al, 2001;Roberts et al, 2001), modulating apoptosis (Florio et al, 1998;Ling et al, 2003), cooperating with the retinoblastoma tumor suppressor pathway (Iavarone et al, 1994;Hara et al, 1996), extending cellular life span (Alani et al, 1999;Nickoloff et al, 2000;Tang et al, 2002), regulating angiogenesis (Lyden et al, 2001) as well as cardiac development (Fraidenraich et al, 2004), and stem cell maintenance (Ying et al, 2003). ID expression is induced as part of the immediate-early transcriptional response to growth factors and is regulated in a cell cycle-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…ID proteins form DNA-binding incompetent heterodimers with bHLH transcription factors thereby inhibiting their transcriptional activities (Benezra et al, 1990). Individual ID-proteins have been linked to inhibiting cellular differentiation, inhibition of bHLHand other transcription factors (Benezra et al, 1990;Jen et al, 1992;Kreider et al, 1992;Ohtani et al, 2001;Roberts et al, 2001), modulating apoptosis (Florio et al, 1998;Ling et al, 2003), cooperating with the retinoblastoma tumor suppressor pathway (Iavarone et al, 1994;Hara et al, 1996), extending cellular life span (Alani et al, 1999;Nickoloff et al, 2000;Tang et al, 2002), regulating angiogenesis (Lyden et al, 2001) as well as cardiac development (Fraidenraich et al, 2004), and stem cell maintenance (Ying et al, 2003). ID expression is induced as part of the immediate-early transcriptional response to growth factors and is regulated in a cell cycle-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…The role of Id2 in heart development (Jen et al, 1996;Fraidenraich et al, 2004) and cardiac conduction system development (Moskowitz et al, 2007) has been previously recognized, but detailed reports on expression patterns of Id2 in the heart, specifically at the venous pole and proximal cardiac conduction system in subsequent embryonic stages, are lacking. Key findings in the current study are (1) the expression of Id2 in cardiac progenitor cells not only at the arterial but also at the venous pole of the heart, including the area of the putative SAN; (2) a severe cardiac phenotype in Id2 knockout embryos with abnormal drainage patterns at the arterial pole (double outlet right ventricle) as well as at the venous pole (abnormal level of drainage of systemic and pulmonary veins) of the heart; (3) congenital heart malformations related to anterior and posterior second heart field deficiency in Id2 knockout embryos.…”
Section: Discussionmentioning
confidence: 99%
“…In the heart, Id2 expression was described in the endocardial cushions of the atrioventricular canal and the outflow tract, the cardiac valves, the epicardium and endocardium, but not the working myocardium (Fraidenraich et al, 2004;Jen et al, 1996). Ablation of two Id-genes in any combination from Id1, 2, or 3 results in severe cardiac defects including ventricular septal defects, thinning of the myocardium, and hypoplastic cushions in the atrioventricular canal and outflow tract (Fraidenraich et al, 2004). In the latter study, no phenotype of single Id2 ablation was observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important difference between ES cells and other progenitors is that the former in theory can give rise to all the cell types in the body, while all other cells have limited plasticity. In a mouse model of congenital heart disease, ES cells have been able to rescue the cardiac defect, 67 and in MI models they have contributed significantly to restoration of cardiac function, with evidence for long-term benefit of ES cell transfer. 68 Multiple issues presently prevent therapeutic application of ES cells in patients, including the need for reliable human ES cell differentiation protocols, purification techniques for the different progeny, circumvention of the immunological rejection of the transplanted cells, and ethical issues centering on the use of human embryos.…”
Section: Resident Cardiac Progenitor Cellsmentioning
confidence: 99%